Integrating Humanity and Technology: Governance of Modern Educational Institutions in the Era of Digital Disruption Through Humanistic-Based Management Information Systems - Esha, Zuhdi; Hasanah, Uswatun; Aiman, Ummu; Abrori, Zumrotul Amalia; Sopiulloh, Wafa; Udin, Tamsik (Jurnal Ar Ro'is Mandalika (Armada), 2024)
The era of digital disruption has introduced a new paradigm in the governance of educational institutions. Challenges are no longer focused solely on administrative efficiency but also on the institution's ability to maintain the humanistic essence within the learning process. This article aims to deeply examine the synergy between effective educational institution governance and the implementation of an Educational Management Information System (EMIS) grounded in a humanistic approach. Through a systematic literature review and conceptual analysis, the article identifies the principles of good governance that must serve as the foundation for educational institutions, including transparency, accountability, responsiveness, fairness, and effectiveness. Furthermore, this article explores the evolution of EMIS from merely an administrative tool to a strategic information ecosystem capable of supporting learning personalization, teacher empowerment, and increased engagement from parents and the community. The main focus of this article is on how EMIS can be designed and implemented not as an instrument of control, but as a means of empowerment for all educational stakeholders students, teachers, staff, and leadership. The analysis also examines implementation challenges, such as the digital divide, human resource readiness, and data security ethics, which are crucial considerations in maintaining the balance between technological innovation and humanistic values. The article concludes that the governance of future educational institutions requires an integrated humanistic technological vision, where technology serves to expand human capacity, not to replace it. Practical recommendations and directions for future research are also presented to provide guidance for education stakeholders in navigating this complex and dynamic landscape.